Ketiadaan Regulasi dan Risiko Kesehatan: Tinjauan Hukum atas Perdagangan Pakaian Bekas dalam Negeri di Indonesia - Cendani, Enggar; Muskibah, Muskibah; Naili Hidayah, Lili (Universitas Jambi, Fakultas Hukum, 2025)
The secondhand clothing trade is becoming increasingly popular in Indonesia, but this practice raises health and legal concerns. Various studies have shown that secondhand clothing contains Staphylococcus aureus bacteria and Aspergillus sp. fungi, which can potentially cause skin infections and other diseases. This condition violates consumers' rights to comfort, security, and safety as stipulated in the Consumer Protection Law (UUPK). This study aims to analyze the legal regulations and forms of consumer protection in the domestic secondhand clothing trade. The method used is normative juridical with a legislative and conceptual approach, as well as a literature review of primary, secondary, and tertiary legal materials. The results show that although the domestic secondhand clothing trade is legal according to the Indonesian Standard Classification of Industrial Fields (KBLI), there are no clear quality and hygiene standards. Existing regulations only provide general protection without specifically regulating quality standards or product information. Therefore, additional regulations are needed that establish quality standards, information obligations, and stricter oversight to protect consumer rights.